Revamp of Grade and Attendance Management Features in the Academic Information System - Yohanes Kevin Wahyu Utama; Generosa Lukhayu Pritalia; Hendro Gunawan; Rangga Perwiratama (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2025)
This study presents the redesign of grade and attendance management features in the Academic Information System (SIAKAD) at Universitas Atma Jaya Yogyakarta (UAJY) using Domain-Driven Design (DDD) supported by the prototyping method. The primary objective is to migrate attendance and grading functionalities from the Employee Performance Assessment System (SPKP) to SIAKAD to enhance academic service quality and operational efficiency. Data collection was conducted through observations and interviews with domain experts, followed by domain modeling to identify specific system requirements. The system architecture was structured into three main bounded contexts: Grade Management, Course Meetings, and Substitute Meetings, each designed following DDD principles to align functionalities with user needs. The design phase incorporated wireframe and prototype mockups to ensure proper system visualization and interaction that meet academic requirements. Implementation was followed by comprehensive Black-Box Testing, including third-party validation, to verify that the new features function according to specifications. The results demonstrate that the revamped system successfully fulfills operational requirements and is ready for deployment, providing improved integration and efficiency in academic administration processes.